The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2106/jbjs.rvw.22.00036
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Outpatient Lower-Extremity Joint Replacement

Abstract: The economics of transitioning total joint arthroplasty (TJA) to standalone ambulatory surgery centers (ASCs) should not be capitalized on at the expense of patient safety in the absence of established superior patient outcomes. » Proper patient selection is essential to maximizing safety and avoiding complications resulting in readmission. » Ambulatory TJA programs should focus on reducing complications frequently associated with delays in discharge. » The transition from hospital-based TJA to ASC-based TJA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…1,2 TJR care delivery is undergoing dynamic changes, with the growth of bundled payment models as well as the shift to outpatient surgery. 3,4 Preoperative patient education is a potentially important element for improving the quality of care in this dynamic landscape 5,6 and is recommended as part of an evidence-based enhanced recovery pathway. 7,8 A few studies have shown components of preoperative TJR education to be related to improvement in specific perioperative metrics such as length of stay, episode costs, preoperative anxiety or expectations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 TJR care delivery is undergoing dynamic changes, with the growth of bundled payment models as well as the shift to outpatient surgery. 3,4 Preoperative patient education is a potentially important element for improving the quality of care in this dynamic landscape 5,6 and is recommended as part of an evidence-based enhanced recovery pathway. 7,8 A few studies have shown components of preoperative TJR education to be related to improvement in specific perioperative metrics such as length of stay, episode costs, preoperative anxiety or expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Total joint replacement (TJR) has been a focus of health care reform given the growing volume and related costs to the health system 1,2 . TJR care delivery is undergoing dynamic changes, with the growth of bundled payment models as well as the shift to outpatient surgery 3,4 . Preoperative patient education is a potentially important element for improving the quality of care in this dynamic landscape 5,6 and is recommended as part of an evidence‐based enhanced recovery pathway 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…3-9 The safety and efficacy of SDD TJA has been established in the intervening 15 years 10-13 with demonstrated reliance on the selection of appropriate patients, avoidance of intraoperative complications, and a clinical team skilled in protocols designed to minimize complications and maximize recovery. 14-17 Consequently, payers have begun to direct qualifying cases to ambulatory surgery center (ASC). Nonetheless, failure to achieve planned SDD for primary TJA occurs in as many as 7% to 49% of patients in the United States.…”
mentioning
confidence: 99%